2015
DOI: 10.1111/sode.12116
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Theory‐of‐mind Coaching and Children's Executive Function Predict the Training Effect of Sociodramatic Play on Children's Theory of Mind

Abstract: Theory of mind (ToM), the ability to interpret one's own and others' mental states, is essential for social interaction; thus, it is important to promote the early development of ToM. The current study investigated (1) whether sociodramatic play (SDP) promotes the development of ToM in kindergarten children; (2) whether teachers' ToM coaching, as well as children's individual differences in language and executive function (EF), may influence how children benefit from SDP; and (3) whether SDP improves children'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 58 publications
1
17
1
Order By: Relevance
“…Additionally, we found that adults’ descriptions had similar impacts on younger and older kindergarten children. These results are consistent with previous findings that, between 4 and 6 years of age, adults can influence children in various respects including what stimuli to attend to, what goal to accomplish, and what perspective to take, as well as influencing their emotion regulation, attribution, and autonomy (e.g., Kesek et al., ; Mattanah, ; Palmer & Wehmeyer, ; Qu et al., ; Qu et al., ). Together with past results, our findings emphasize the important transient feature of the kindergarten period, during which children rapidly develop the ability to regulate their behaviors but still seek information and support from their parents and teachers (e.g., Rimm‐Kaufman et al., ; Zimmer‐Gembeck & Skinner, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, we found that adults’ descriptions had similar impacts on younger and older kindergarten children. These results are consistent with previous findings that, between 4 and 6 years of age, adults can influence children in various respects including what stimuli to attend to, what goal to accomplish, and what perspective to take, as well as influencing their emotion regulation, attribution, and autonomy (e.g., Kesek et al., ; Mattanah, ; Palmer & Wehmeyer, ; Qu et al., ; Qu et al., ). Together with past results, our findings emphasize the important transient feature of the kindergarten period, during which children rapidly develop the ability to regulate their behaviors but still seek information and support from their parents and teachers (e.g., Rimm‐Kaufman et al., ; Zimmer‐Gembeck & Skinner, ).…”
Section: Discussionsupporting
confidence: 92%
“…First, an adult can influence kindergarten children's perceptions and interpretations of an external situation. An adult can help frame the event, guiding children as to what features to attend to in the situation (e.g., Mischel & Baker, ), what perspectives to take (e.g., Qu, Shen, Chee, & Chen, ; Recchia & Howe, ), what outcomes to expect, and what causes to suspect (e.g., Mattanah, ). Second, an adult can help kindergarteners reflect on their own condition and, in particular, on their own essential goals and abilities.…”
Section: Adults Can Influence Kindergarten Children's Appraisal and Fmentioning
confidence: 99%
“…In addition to the above-mentioned predictor variables, we included age, gender and ToM skills as control variables in the analyses, as gender differences in the type of play and in the activities and themes of choice were also found (Power, 2011). Furthermore, studies indicate that there are significant associations between children's ToM skills and their pretend play level (Lillard et al, 2013;Qu et al, 2015).…”
Section: The Current Studymentioning
confidence: 99%
“…Re-description theory applies to ToM too. When children are in the process of understanding mental states, they need to understand that a certain event can be represented and viewed differently (Qu et al, 2015). Thus, children’s ToM might be improved by promoting children’s representation, whit the support of narrative tasks.…”
Section: Introductionmentioning
confidence: 99%